Ethnobotanical Knowledge of Sterculia setigera Del. in the Sudanian Zone of Togo (West Africa). (14th November 2012) - Atakpama, Wouyo; Batawila, Komlan; Dourma, Marra; Pereki, Hodabalo; Wala, Kpérkouma; Dimobe, Kangbéni; Akpagana, Koffi; Gbeassor, Messanvi
Abstract : Ethnobotanical knowledge is useful in development of management and conservation of plant genetic resources. In this study, ethnobotanical investigations were conducted in Sudanian zone of Togo to identify use values knowledge of Sterculia setigera tree. Information was obtained with the aid of semistructured interviews. Three (3) ethnic groups: Bassar, Moba, and Konkomba belonging to ten (10) localities were investigated. Use knowledge of Sterculia setigera through these ethnic groups was assessed using four use indices: reported use (RU), plant part value (PPV), specific reported use (SU), and intraspecific use value (IUV). Sixty (60) informants of 43 years old were interviewed. The plant parts values and specific uses are raised more in the Moba's ethnic group. The main quoted uses are medicinal, religious, food, and cosmetic. Thus, fourteen (14) treatments of ailments are assigned to it. Considering the various uses, it is crucial to validate scientifically the therapeutic uses and safety of these plants through phytochemical screening, different biological activity tests, and toxicological studies.